Māui And The People Of The North - Jones, Carwyn (Victoria University of Wellington Law Review, 2013)
This story was inspired by my participation in a workshop on Indigenous Legal Traditions held in Fort St John, British Columbia, Canada, in 2011. At that workshop, lawyers and legal academics worked collaboratively with elders and other members of the local region’s Cree and Dene communities over several days to explore ways of reading and working with indigenous legal ’texts’. Though the workshop was necessarily tentative and exploratory, there were powerful learnings for all involved and I would like to acknowledge the generosity of the peoples of the Treaty Eight territory for sharing their stories with all of us who were privileged to participate.